LINEAR GROWTH OF PLANTS AND SOME MORPHOLOGICAL FEATURES OF CORN - O. Botirov (Scholars Digest Publishing, 2023)
The carried out quantitative accounts of the influence of the studied forms and norms of phosphorus-containing fertilizers on the morphological characteristics of corn show that the highest indicators for the linear growth of plants, the height of the laying of the cob and the diameter of the stem at the 2nd internode were provided with the introduction of phosphorus fertilizers of the polyphosphate type, both unwashed and and in washed out typical serozem.
Keywords: corn, soil, plants, unwashed, washed off, fertilizers, phosphorus, forms, norms, growth.